2016
DOI: 10.1039/c5ra23344e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and fabrication of ultrathin iron pyrite (FeS2) thin films and field-effect transistors

Abstract: We report the synthesis of an ultrathin FeS2thin filmviathermal sulfurization of an iron thin film. The FeS2based transistor not only broadens the applications of pyrite, but also provides a platform for investigating FeS2materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Pyrite has wide area of applications (Figure ) such as energy storage and conversion field: photovoltaics,, photocatalytic hydrogen production, batteries, supercapacitors, photocapacitors, thermoelectricity;, electronics,, optoelectronics, spintronics; environmental applications; hydrogenation; sensors; agriculture, and emerging biomedical field …”
Section: Introductionmentioning
confidence: 99%
“…Pyrite has wide area of applications (Figure ) such as energy storage and conversion field: photovoltaics,, photocatalytic hydrogen production, batteries, supercapacitors, photocapacitors, thermoelectricity;, electronics,, optoelectronics, spintronics; environmental applications; hydrogenation; sensors; agriculture, and emerging biomedical field …”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectrum (Figure b) showed three peaks at 332, 372, and 420 cm –1 . These are the characteristic active modes for FeS 2 corresponding to the S2 vibration ( E g ), S–S in-phase stretch ( A g ), and coupled vibration and stretch ( T g ) modes, respectively . This clearly shows that there is no extra peak of other phases like trolite (210, 280 cm –1 ), pyrrhotite (214 and 282 cm –1 ), and maracasite (428 cm –1 ) .…”
Section: Results and Discussionmentioning
confidence: 87%
“…Further, no other diffraction peak was observed in the XRD pattern of Ann.FeS 2 except for the substrate peak of ITO. This indicates that the FeS 2 nanoparticle exhibited a single-phase cubic pyrite structure . The XRD pattern of Ann.TiO 2 (Figure S1b) showed that diffraction peaks well matched with JCPDS card no.…”
Section: Results and Discussionmentioning
confidence: 90%
“…To improve these characteristics, the metal foam needs to be treated with a material with structural characteristics similar to those of the active material of the cathode. Fe metal foam is a promising option because it can react with S 2 powders to form FeS 2 , a thermal battery cathode material, via simple thermal sulfidation, as shown in Figure 1 (Ferrer and Sánchez, 1991;Liu et al, 2016). The purpose of this study is to synthesize a cathode frame whose structural characteristics are the most similar to those of cathode materials (FeS 2 ) of thermal batteries.…”
Section: Introductionmentioning
confidence: 99%